Health Perceptions, Stroke Risk and Readiness for Behavior Change: Gender Differences in Young Adult African Americans - Aycock, Dawn M. (J Racial Ethn Health Disparities, 2019)
The presence of traditional cardiovascular risk factors has increased among young African American (AA) adults, making them more susceptible to stroke. We examined baseline data from the Stroke COunseling for Risk REduction (SCORRE) study to describe health perceptions, stroke risk, and readiness for behavior change along with gender differences in a cohort of young AA. Self-administered questionnaires were used to assess perceptions of general health, stroke risk, competence to live a healthy lifestyle and readiness for behavior change. Actual stroke risk was measured using the American Heart Association (AHA) Life’s Simple 7® (LS7) program. Data were collected from 116 participants (86 women, 30 men) who had a mean age of 24.6 (SD = 4.5). On average participants had 2.6 (SD = 1.1) out of 7 risk factors for stroke, rated their overall health at the midpoint of the scale (“good”), perceived a low risk of future stroke, felt competent they could live a healthy lifestyle, and were not at a stage of readiness for behavior change. A significantly higher proportion of men than women met AHA recommendations for physical activity (77% vs. 49%; p<.01), but had blood pressure readings ≥ 120/80 (70% vs. 34%; p<.01), and smoked cigarettes/cigars (20% vs. 2% p<.01). Fewer men than women were at a stage of readiness for behavior change to reduce stroke risk (13% vs. 40%; p<.01). Stroke risk needs to be assessed early in AA and the LS7 can be used to assess and communicate risk. Understanding gender differences may help with tailoring stroke prevention education and treatment programs.